Ambraser Heldenbuch Gesamttranskription mit Manuskriptbild - Teilband 1 - Höfische Texte - Klarer, Mario (Transcriptiones, 2021)
The "Ambras Book of Heroes," commissioned by Maximilian I, is one of the most important sources of medieval German literature. In this eleven-volume complete edition, all 25 texts from the codex appear in print for the first time in their original Early New High German wording - for 15 of which there is only a singular transmission. Alongside a precise, diplomatic transcription, this edition also provides additional manuscript scans.